Lexical and Syntactic Development of Dizygotic Persian-Speaking Twins from 21 to 31 Months - Hassan Bashirnezhad; Somayeh Mohammadi (̒Ilm-i Zabān, 2021)
The present study examines the lexical and syntactic development of dissimilar Persian-speaking twins named Behzad and Behnam over a period of ten months (from the beginning of 21 months to the beginning of 31 months). This study seeks to find out what differences and similarities there are in the syntactic and lexical development of these twins, despite the fact that the two children grow up in the same language environment. The data of this study were collected through rapid observation and recording of data in a notebook, audio and video recording using a video camera and audio recorder, as well as the diary of the mother of the twins in which children's language products were recorded. The investigation of the collected data and their comparative analysis each month shows a significant difference between the lexical and syntactic development of the twins. Although in the early months of the study, Behzad had a much higher language ability compared to his twin brother, Behnam, from the fourth month of the study, a significant increase in Behnam's lexical and syntactic growth rate was observed. Considering that the language development environment of these two children, both in the family and in the kindergarten, has often been the same, the existence of differences in the lexical and syntactic developmental stages of these two children can be attributed to the difference in innate and inherited linguistic talent of these two children. Dizygotic twins do not have exactly the same chromosomal structure. The results of this study show creative mental activities in two children, which is evidenced by the existence of numerous cases of over-extension and overgeneralization.